On I- Deferred Statistical Convergence of Order ? - Sengul, Hacer; Et, Mikail; Isik, Mahmut (Univ Nis, Fac Sci Math, 2019)
The idea of I-convergence of real sequences was introduced by Kostyrko et al. [Kostyrko, P., Salat, T. and Wilczynski, W. I-convergence, Real Anal. Exchange 26(2) (2000/2001), 669-686 ] and also independently by Nuray and Ruckle [Nuray, F. and Ruckle, W H. Generalized statistical convergence and convergence free spaces. J. Math. Anal. Appl. 245(2) (2000), 513-527]. In this paper we introduce I-deferred statistical convergence of order a and strong I-deferred Cesaro convergence of order a and investigated between their relationship.
Keywords: Statistical convergence; I-convergence; Cesaro summability